2004
DOI: 10.1111/j.1440-0979.2004.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing increased demand for mental health services in a public hospital emergency department: A trial of ‘Hospital‐in‐the‐Home’ for mental health consumers

Abstract: Increasing demand from mental health consumers for crisis assessment and intervention in public Emergency Departments (ED) has placed considerable strain on the resources of the ED and long delays awaiting admission are experienced. At Flinders Medical Centre in South Australia, the Psychiatry Department trialled a 'hospital-in-the-home' service to relieve the pressure on the ED and enhance inpatient capacity. The trial has been successful in diverting mental health consumers directly to intensive home-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 9 publications
1
30
0
3
Order By: Relevance
“…Consistent with the findings of another Australian study [14], those of the present study may indicate that the absence of community-based CAT teams does not increase demand for emergency department services. Reporting on the changes to the model of care at Flinders Medical Centre in South Australia, Kalucy et al showed that a hospital-in-thehome service for mental health consumers was successful in diverting consumers from the emergency department and freed up inpatient beds.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings of another Australian study [14], those of the present study may indicate that the absence of community-based CAT teams does not increase demand for emergency department services. Reporting on the changes to the model of care at Flinders Medical Centre in South Australia, Kalucy et al showed that a hospital-in-thehome service for mental health consumers was successful in diverting consumers from the emergency department and freed up inpatient beds.…”
Section: Discussionsupporting
confidence: 92%
“…29 In a trial of a "hospital in the home" service to relieve pressure on EDs, the authors reported positive outcomes on redirecting patients to intensive community-based mental health services, freeing up beds in the ED. 30 Due to limitations of the available database, comorbid substance abuse by patients with mental health issues in the ED was not studied. The association between comorbid substance abuse and psychiatric disorders presenting to a general hospital ED has been associated with substantially increased ED service usage.…”
Section: Models Of Carementioning
confidence: 99%
“…The change in treatment preference has dramatically impacted upon the burden of care experienced by the family who have swiftly obtained responsibility from the mental health institutions to manage their care (Brand 2001; Carne 1993). Hospitalization of people with mental illness has also become brief as a result of a reduction in inpatient beds (Kalucy et al . 2004).…”
Section: Introductionmentioning
confidence: 99%